การวัดเชิงสัณฐานของปมประสาทซีลีอารี่ที่เกี่ยวข้องกับการประยุกต์ทางคลินิก - ลิตา เทสาภิรัติ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Ciliary ganglion can be easily injured without notice in many intraorbital procedures. It lays posterolateral in the orbit; the surgical procedures approaching lateral side of the orbit are always associated with the ciliary ganglion injury which may results in transient mydriasis and tonic pupil. 40 embalmed cadaveric globes were dissected under surgical loupe to observe characteristics of roots reaching the ciliary ganglion, number of short ciliary nerve, location of the ciliary ganglion in the orbit. Morphometry of the ciliary ganglion and distances between the ciliary ganglion and important landmarks were measured. The ciliary ganglion located near orbital apex, lateral to optic nerve and medial to lateral rectus muscle. The mean width of the ciliary ganglion was 2.24 mm and the mean diameter from anterior edge to posterior edge was 3.50 mm. The mean distances from the ciliary ganglion to posterior end of globe, lateral rectus muscle, optic nerve and the scleral insertion of the lateral rectus muscle were 16.04 mm, 2.88 mm, 1.47 mm and 31.53 mm, respectively. Moderate inverse correlation was found between the distance from the ciliary ganglion to posterior end of globe and the distance between the ciliary ganglion and the lateral rectus muscle. The number of motor root could be 1,2 and also 3 roots which had not been reported. Sensory root was found only 1 root in every specimen. Sympathetic root could be observed 1 root in most of the specimens. The number of short ciliary nerves was 6-14 nerves. This anatomical knowledge should be concerned in intraorbital procedures to reduce complication of the ciliary ganglion injury. The new measurement from the ciliary ganglion to scleral insertion of lateral rectus muscle could be applied in intraorbital surgeries and also in botulinum toxin injection to ocular muscles.